2021
DOI: 10.1038/s41398-021-01196-y
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of depressive and anxiety symptoms and their associations with quality of life among clinically stable older patients with psychiatric disorders during the COVID-19 pandemic

Abstract: The impact of the COVID-19 pandemic on clinically stable older patients with psychiatric disorders is unclear. This study examined the prevalence of depressive and anxiety symptoms, and their associations with quality of life (QOL) in clinically stable older patients with psychiatric disorders during the COVID-19 pandemic. This was a multicenter, cross-sectional study. Depressive and anxiety symptoms, insomnia, pain, and QOL were assessed with standardized instruments. A total of 1063 patients were included. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
46
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 70 publications
7
46
1
2
Order By: Relevance
“…Similarly, another study also revealed a negative association between worries of COVID-19 and SWB, which was mediated through future anxiety (Paredes et al, 2021 ). In China, a recent study demonstrated that during the pandemic, the symptoms of depression and anxiety were negatively associated with quality of life (Li et al, 2021 ). While it was argued that the Asian countries was generally outperforming the Western world in controlling the pandemic (Landoni et al, 2020 ), the stringent lockdown and social distancing measures implemented in these Asian regions also exerted a great adverse impact on the economic situation and psychosocial well-being of individuals, especially for the vulnerable groups (Marmot & Allen, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, another study also revealed a negative association between worries of COVID-19 and SWB, which was mediated through future anxiety (Paredes et al, 2021 ). In China, a recent study demonstrated that during the pandemic, the symptoms of depression and anxiety were negatively associated with quality of life (Li et al, 2021 ). While it was argued that the Asian countries was generally outperforming the Western world in controlling the pandemic (Landoni et al, 2020 ), the stringent lockdown and social distancing measures implemented in these Asian regions also exerted a great adverse impact on the economic situation and psychosocial well-being of individuals, especially for the vulnerable groups (Marmot & Allen, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID- 19) is a respiratory illness that resulted in an outbreak in December 2019 and progressed to pose a global pandemic. This virus is one of the six species under a family of enveloped, single-stranded RNA viruses known as the Coronaviridae [1].…”
Section: Introductionmentioning
confidence: 99%
“…Prior research regarding specifically the mental health outcome of psychogeriatric patients has provided contradictory results. One study of older adults with pre-existing depression did not report an increase in symptoms of depression and anxiety within this group [ 13 ] whereas Li et al noted that among clinically stable psychogeriatric patients prevalence of depression and anxiety during the pandemic were higher than in other age groups [ 14 ].…”
Section: Introductionmentioning
confidence: 99%